Investing in trust is crucial for a well-functioning European carbon market - Vincent de Gooyert; Senni Määttä; Sandrino Smeets; Heleen de Coninck (Earth System Governance)
Emission reductions needed to reach the Paris Agreement goals rely heavily on carbon dioxide capture and storage (CCS). However, CCS implementation is lagging due to complex interactions of societal and technological factors. Attempts to enhance CCS implementation focus primarily on lowering technological and economic barriers, assuming that societal support will develop if public awareness is increased. This, however, overlooks the interdependence between CCS public support, policy action and industrial implementation. Productive interaction between these factors requires mutual trust between stakeholders. Scaling up the technology will thus require appreciating the mutual dependencies and nurturing trust. Genuine investments in public trust go beyond ‘educating the public’, supporting deliberative initiatives instead and allowing for real influence of relevant stakeholders. Our recommendations include designing inclusive engagement processes, safeguarding public participation rights, involving independent scientific expertise, supporting deliberative initiatives like citizen assemblies, and fostering transparency through community-led platforms to build trust in CCS implementation.